Untying the knot : making peace in the Taiwan Strait - Bush, Richard C., 1947- (Brookings Institution Press, 2005)
"A comprehensive analysis of the paradoxical relationship between Taiwan and China, characterized by social and economic interaction and political and military tensions, and the diplomatic diffidence of the United States in the face of its high strategic stakes"--Provided by publisher.
Keywords: Taiwan -- Relations -- China.; China -- Relations -- Taiwan.; Taiwan -- Relations -- Chine.; Chine -- Relations -- Taiwan.; 89.70 international relations: general.; 15.75 history of Asia.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE -- International Relations -- Diplomacy.; International relations; China; Taiwan; Politischer Konflikt; Foreign relations.; China.; Taiwan.; International relations.; Taiwan -- foreign policy -- China.; China -- military strategy -- regional conflicts -- conflict resolution -- national security -- Taiwan.; 1980-1990.; 1990-2000.; 2000-2010.